The Potential of Scientific Research Support and Its Role in Enhancing the Competitiveness of Universities “Zarqa University as Case Study”2001-2013 (International Journal of Management and Sustainability, 2015)
Change has become a modern-day feature, affect all human societies components, as organizations became one of the main components of human society, the ability of organizations to success is determined by its ability to deal with those variables positively and effectively. higher education institutions as a leader of knowledge and producer of it, it is also eligible for change like other organizations by different political, economic and social dimensions, , and many of the issues that were higher education institutions distance themselves from dealing with it, it became inevitable seen as a determinant of its ability to continue and survive. In this context, concepts such as market competition and customers have become importance issues and necessity in higher education institutions. In contrast the development is the most important issues related to developing economies, especially Arab ones, and since the development beyond the concept of capital development and production to human development intellectually and scientifically, the necessity require attention to this activity, which is a fundamental pillar for the development of the economy, the higher the level of development or activation of scientific research and technological development efficiently, the higher the level of progress in the economy. The researcher study the impact of financial Fund provided by universities to Academic stuff on the competitiveness of higher education institutions expressed by the development of student numbers on one hand and the level of educational attainment for students. For this purpose, the researcher chose Zarqa University of Jordan as a model for the study. Using descriptive approach and statistical analysis program, The Pearson’s correlation coefficient was used to analyse data and level of significance was set at the (0.01) level. Results of this study indicate that there is a positive relationship between scientific research support provided by Zarqa University and the competitiveness of Zarqa University.